2020
DOI: 10.3389/fmicb.2020.571831
|View full text |Cite
|
Sign up to set email alerts
|

Medusavirus Ancestor in a Proto-Eukaryotic Cell: Updating the Hypothesis for the Viral Origin of the Nucleus

Abstract: The mechanistic evolutionary origin of the eukaryotic cell nucleus remains unknown. Among several plausible hypotheses, the most controversial is that large DNA viruses, such as poxviruses, led to the emergence of the eukaryotic cell nucleus. Several recent findings, including the discovery of a nucleus-like structure in prokaryotic viruses and prokaryotes possessing nucleus-like inner membranes, suggest genomic DNA compartmentalization not only in eukaryotes but also in prokaryotes. The sophisticated viral ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
1
19
1
2
Order By: Relevance
“…These results suggest that Mirusviricetes viruses influence the ecology of key marine eukaryotes, albeit probably not to the same extent as the more diverse and abundant class of Megaviricetes. Moving forward, the comprehensive marine genomic database for Nucleocytoviricota we built, which includes Mirusviricetes and Proculviricetes, may help solve many hypotheses that orbit around these large and giant DNA viruses, from their potential roles in the emergence and evolution of eukaryotes 14,15,[41][42][43][44] , to their regulation of ecologically critical marine eukaryotes 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that Mirusviricetes viruses influence the ecology of key marine eukaryotes, albeit probably not to the same extent as the more diverse and abundant class of Megaviricetes. Moving forward, the comprehensive marine genomic database for Nucleocytoviricota we built, which includes Mirusviricetes and Proculviricetes, may help solve many hypotheses that orbit around these large and giant DNA viruses, from their potential roles in the emergence and evolution of eukaryotes 14,15,[41][42][43][44] , to their regulation of ecologically critical marine eukaryotes 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…NCLDVs also impact the evolution of their hosts via lateral gene transfers, since for instance, up to 10% of genes were identified as originating from NCLDVs among the green algae 12 . They could have also been driving the evolution of eukaryotes (including the emergence of complex proto-eukaryotic traits) through a long-standing coevolution [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The fact that social heterosis can occur and social genomes may arise analogously in both quasi-species swarms of RNA viruses and cancer tumours leads to interesting evolutionary comparisons. Viruses and their hosts have been in a several billion-year coevolutionary arms race from perhaps the origin of life on Earth [ 132 ]. This arms race, however, is evolutionarily balanced.…”
Section: Discussionmentioning
confidence: 99%
“…They have been classified within the phylum Nucleocytoviricota (also referred to as nucleo-cytoplasmic large DNA viruses [NCLDVs]) ( 7 ). Phylogenetic analyses suggested that the diversification of this group of viruses predated the emergence of modern eukaryotic lineages ( 8 , 9 ), which revived the debate about their evolutionary origin ( 10 , 11 ) and their relationship to the genesis of the eukaryotic nucleus ( 12 , 13 ). Genomic analysis revealed a large number of genes (referred to as orphan genes) without detectable homology to any known genes.…”
Section: Introductionmentioning
confidence: 99%